THE ROLE OF BRAND TRUST IN MEDIATING INFLUENCE OF SOCIAL MEDIA MARKETING AND EWOM ON CULINARY PURCHASE DECISION IN BALI: A STUDY OF @FOODBALI SOCIAL MEDIA FOLLOWERS - Kusumasari N.M.I.; Ekawati N.W.; Piartrini P.S.; Aksari N.M.A. (Eurasia: Economics & Business, 2023)
The rapid growth in the number of restaurants in the city of Denpasar provides many alternative choices for consumers, so they need information as a reference, one of which is through social media which can help encourage consumer purchase decision. The large number of consumers looking for culinary information on social media has also become an opportunity for business people such as restaurants or cafes to share their business on social media such as Social media. Through this, the level of competition in the culinary business becomes increasingly fierce and various efforts are made by culinary entrepreneurs to attract consumers. One of the strategies carried out is in collaboration with culinary media @foodbali. The purpose of this study is to shed light on how consumers' trust in brands affects the effectiveness of social media marketing and word-of-mouth while making decisions about food and drink in Bali. In this study, we collected data from people who follow the Social media account @Foodbali. The sample size is 128, and the sampling technique is purposive sampling, which is not based on probability. The data is gathered through the use of a Google Form questionnaire that is shared throughout various social media platforms. Structural Equation Modeling (SEM) using Partial Least Square (PLS) is the method used to analyze the data in this study. According to the findings, there is a positive and statistically significant connection between social media marketing and consumer spending, as well as between electronic word of mouth and consumer spending, social media marketing and brand trust, electronic word of mouth and brand trust, brand trust and consumer spending, and social media marketing and brand trust. Based on the results of this research, it is hoped that the results of this research will be able to increase the development of marketing management knowledge, especially related to consumer behavior, as well as become a reference for marketers and entrepreneurs in the culinary sector to further increase the application of social media marketing, EWOM, brand trust in collaboration with foodblogger culinary information media so that can improve consumer purchase decision.